Transfer Pricing Policy among Foreign Companies; from Creativity to Innovation and Sustainability - Heryani, Ani; Fauzi, Muhammad; Kurniawan, I Made Gede Ariestova; Hendriarto, Prasetyono; Fatmawati, Endang (Budapest International Research and Critics University, 2022)
The transfer pricing policy of every company operating in various countries certainly has differences and similarities in a very creative way towards innovation and high mobility, and they must comply with strategic rules and policies. Our data is obtained from a database of scientific journals, books, and other relevant literature to answer the study questions. After the data is collected, proceed with critical analysis, systematic coding, and relevant conclusions in answering the core issue, namely the transfer pricing policy in every foreign company. Based on the discussion and analysis of the data, we can conclude that every company operating in various countries has policies and rules regarding implementing transfer pricing. Their goal is that through the formulation of policies and execution of transfer pricing, they are always inseparable from creativity and innovation so that their company can be sustainable. Thus, the outcomes of this review may be useful as insight to efforts to develop similar studies in the future.